Evaluation of the Chagas VirClia® and Chagas TESA VirClia® for the Diagnosis of Trypanosoma cruzi Infection - Isabel García-Bermejo; David Molina Arana; Gloria Zaragoza Vargas; Blanca Carrasco Fernández; Emilia García; Javier Nieto; Maria Delmans Flores-Chávez (Pathogens, 2022)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi, is an important problem of public health even in regions where it is not endemic. Spain ranks second worldwide in terms of imported cases of T. cruzi infection in the chronic phase. The diagnosis in this stage is made via the detection of antibodies against T. cruzi. Therefore, we aimed to evaluate the sensitivity and specificity of two fully automated chemiluminescence immunoassays, Chagas VirClia® (CHR), which uses a mixture of recombinant antigens, and Chagas TESA VirClia® (TESA), the first chemiluminescence assay based on excretion-secretion antigens of trypomastigotes, both designed in monotest format. A retrospective case–control study was performed using 105 well-characterized samples: 49 from patients with CD, 22 from uninfected individuals, and 32 from patients with other pathologies. Sensitivity was 98% for CHR and 92% for TESA. In contrast, the specificity in both was 100%. Cross-reactivity was observed in leishmaniasis (2/10). CHR meets the criteria to become a tool for serological screening, while TESA has the potential for confirmation and cross-reaction discrimination. The monotest format allows its application in laboratories with a small number of samples. The high specificity of both assays is useful in areas where leishmaniasis is endemic.